Analisis Senyapan pada Produksi Ujaran Ayah Mirna dalam Video "Jessica Divonis Membunuh Mirna. Ayah Mirna: Happy Ending I Win!" - Isabella, Nur Laili; Wahyuningtyas, Putri; Nabila, Rahma Nurlina (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2024)
This research was conducted to describe the silence that occurs in speakers' speech production. This research also aims to describe the factors that cause silence in speech made by speakers. This research method uses qualitative research methods using primary data in the form of the recitation of Mirna's father in the video entitled Jessica Convicted of Killing Mirna. Mirna's father: "Happy ending, I win!" Data analysis used in this research uses Miles and Huberman (2014) model analysis, namely collecting all notes in the field, then analyzing and classifying the types of silence uttered by Mirna's father in the video, then presenting them to in the pattern that is formed, to produce conclusions and answer the problem being researched. The results of this research found 50 analysis data that had two types of silence, namely silent silence and filled silence. There are three positions of silence, namely grammatical pauses, between constituents, and before the main word in a constituent. Apart from that, three factors were found to cause silence, namely because the speaker forgot the necessary words, the speaker had already started speaking, but was not ready for the entire sentence, the speaker was very careful in choosing words so as not to cause a negative effect.